Dietary Diversity Practice and Associated Factors Among Infants and Young Children in Haramaya Town, Ethiopia - Berhe Gebremichael; Gudina Egata; Nega Assefa (Intelektual Pustaka Media Utama, 2017)
Optimum child feeding is crucial for growth, development, and better health in later life. Dietary diversity is a critical part of the feeding practices. However, there is limited evidence on dietary diversity practice in low-income countries, like Ethiopia. This study assessed dietary diversity practice and associated factors among mothers of infants and young children aged 6-23 months in Haramaya Town, Eastern Ethiopia. Community based cross-sectional study design was used and study participants were selected by simple random sampling. Data were collected using a pre-tested questionnaire by face-to-face interview. The collected data were entered to EpiData version 3.1 and exported to SPSS version 22.0 for analysis. Characteristics of the study participants were described by using frequencies, percentages, summary measures, and tables. Bi-variable and multi-variable analyses were used to identify the associated factors. Statistical significance was declared at p-value < 0.05. The study included 635 participants yielding to a response rate of 98.1%. The prevalence of dietary diversity practice was 25.2%. Mothers learned up to secondary level or above [(AOR=2.97, 95% CI: (1.26, 6.99)], mothers who had job [(AOR=3.21, 95% CI: (1.41, 7.29)], older children [(AOR=2.51, 95% CI: (1.45, 4.34)], male children [(AOR= 2.08, 95% CI: (1.29, 3.33)], healthy children [(AOR=2.65, 95% CI: 1.36, 5.16)] and richest households [(AOR=4.45, 95% CI: 1.94, 10.22)] were associated with dietary diversity practice. Generally, the dietary diversity practice was low. Therefore, attention should be given to mothers with no formal education and efforts should be done to improve the socioeconomic status of the households.